Efeito da época sobre a emergência de Sida rhombifolia e Solanum viarum em diferentes profundidades de semeadura - Souza, Marcelo Claro [UNESP] (2012)
Knowing the ideal depth for germination of weed seed is important for the development of efficient, safe and economical management strategies. In order to study the effects of the seasonality on the seedling emergence of Sida rhombifolia L. and Solanum viarum Dunal, two experiments were conducted in greenhouse conditions during September 2008 and January 2009. Seeds of both species were sown at different depths (0, 1, 2, 3, 4 and 5 cm). Sida rhombifolia was less sensitive to seasonal variations, and the highest percentages of emergence occurred between 1 and 4 cm depths. It was observed strong seasonality influence on the emergence of S. viarum. For this species highest emergency was observed in the greater depths, and the lowest for seeds located on the soil surface.